Recent review on porous adsorbents for water decontamination: strategies for enhanced removal of tetracycline - Zheng, Alvin Lim Teik; Teo, Ellie Yi Lih; Seenivasagam, Sivasangar; Yiu, Pang Hung; Boonyuen, Supakorn; Chung, Eric Lim Teik; Andou, Yoshito (Springer, 2024)
The growing contamination of water sources by tetracycline (TC) antibiotics presents significant environmental and public health challenges. Porous adsorbents, including metal-organic frameworks (MOFs), graphene (Gr), biochar (BC), clay, zeolites, and porous polymers, have emerged as promising solutions due to their high surface area, tunable porosity, and modifiable chemistry. This review systematically explores recent advancements in the design and modification of these materials to enhance their efficiency in TC removal from water. Key strategies such as surface functionalization, composite formation, and doping are discussed, emphasizing their impact on TC adsorption capacity and performance. Additionally, the review addresses the practical challenges of implementing these modified adsorbents, including regeneration, cost-effectiveness, and environmental sustainability. Synergistic approaches combining multiple modification techniques are highlighted as pathways to next-generation adsorbents with superior performance. This work provides a comprehensive understanding of the state-of-the-art in porous adsorbent technology for antibiotic remediation, pointing towards innovative solutions for water decontamination and future directions in environmental pollution control. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.